Research on Shear Capacity and Checking Method of MT·G-Joint for Application in Prefabricated Underground Structures - Xiuren Yang; Zhongheng Shi; Fang Lin (Advances in Materials Science and Engineering)
The MT·G-Joint (grouted mortise-tenon joint), invented as the connection between the large prefabricated elements, is the most important component in the prefabricated underground structures. Its shear performance is critical to the overall mechanical performance of the prefabricated structure. This paper carries out four-point pure shear experiment to investigate the shear performance of the MT·G-Joint. The shear key method is then proved to be suitable for MT·G-Joint when the axial load is 0 kN based on the experimental results. In addition, combining the shear key method and experimental results, the calculation method of the shear capacity, improved shear key method (ISKM), is proposed on account of the mechanical model of the failure plane. ISKM is appropriate for different load conditions. Finally, every kind of joints used in the prefabricated metro station structures on Changchun Metro Line 2 is calculated by using ISKM. The results indicate that the shear capacity of the MT·G-Joint is good, and the used joints still have large safety margin even under the worst working condition. The findings of this study are of value to help researchers and engineers more effectively design prefabricated underground structures.